Global Monitoring Report 2004 : Policies and Actions for Achieving the Millennium Development Goals and Related Outcomes. (World Bank Group, 2004)
The elements of the World Bank's millennium development goals include eradicating extreme poverty and hunger, achieving universal primary education, promoting gender equality, improving child and maternal health, combating disease, ensuring environmental sustainability, and developing global partnerships for development.